Analisis Kualitatif Harapan dan Realita: Persepsi Mahasiswa terhadap Laboratorium Konseling - Freddi Sarman; Yulianti (EMPATI: Jurnal Bimbingan dan Konseling, 2025)
The low utilization of the counseling laboratory affects the effectiveness of its services. This study aims to analyze students' perceptions, expectations, as well as the reality of the counseling laboratory. A qualitative research approach was used, with data collected through interviews and observations. The research subjects were students who had utilized the counseling laboratory as part of their academic activities. The findings on students' perceptions regarding the implementation of the Counseling Laboratory reveal a gap between expectations and reality. The study found that the laboratory has not fully met students' expectations, particularly in terms of suboptimal facilities and a lack of faculty supervision. Factors contributing to this gap include the quality of laboratory facilities. These findings highlight the need for improvements in facilities and supervision to enhance the effectiveness of counseling laboratory services.